M6A RNA Methylation Regulator HNRNPC Contributes to Tumorigenesis and Predicts Prognosis in Glioblastoma Multiforme - Wang, Li-chong; Chen, Shu-hui; Shen, Xiao-li; Li, Dang-chi; Liu, Hai-yun; Ji, Yu-long; Li, Min; Yu, Kai; Yang, Huan; Chen, Jun-Jun; Qin, Chong-zhen; Luo, Ming-ming; et al. (Frontiers in Oncology, 2020)
Glioblastoma multiforme (GBM) is the most malignant glioma with a high death rate. N6-methyladenosine (m6A) RNA methylation plays an increasingly important role in tumors. The current study aimed to determine the function of the regulators of m6A RNA methylation in GBM. We evaluated the difference, interaction and correlation of these regulators with TCGA database. HNRNPC, WTAP, YTHDF2, YTHDF1 were significantly upregulated in GBM. To explore the expression characteristics of regulators in GBM, we defined two subgroups through consensus cluster. HNRNPC, WTAP, YTHDF2 were significantly upregulated in the cluster2 which had a good overall survival (OS). To investigate the prognostic value of regulators, we used lasso cox regression algorithm to screen an independent prognostic risk characteristic based on the expression of HNRNPC, ZC3H13 and YTHDF2. The prognostic feature between the low and high-risk groups was significantly different (P<0.05), which could predict significance of prognosis (area under the curve (AUC)=0.819). Moreover, we used western blot, RT-PCR, and immunohistochemical staining to verify the expression of HNRNPC was associated with malignancy and development of gliomas. Similarly, the high expression of HNRNPC had a good prognosis. In conclusion, HNRNPC is a vital participant in the malignant progression of GBM and might be valuable for prognosis.